Differential Regulation of Human Surfactant Protein A Genes, SFTPA1 and SFTPA2, and Their Corresponding Variants - Floros, Joanna; Tsotakos, Nikolaos (Frontiers in Immunology, 2021)
The human SFTPA1 and SFTPA2 genes encode the surfactant protein A1 (SP-A1) and SP-A2, respectively, and they have been identified with significant genetic and epigenetic variability including sequence, deletion/insertions, and splice variants. The surfactant proteins, SP-A1 and SP-A2, and their corresponding variants play important roles in several processes of innate immunity as well in surfactant-related functions as reviewed elsewhere [1]. The levels of SP-A have been shown to differ among individuals both under baseline conditions and in response to various agents or disease states. Moreover, a number of agents have been shown to differentially regulate SFTPA1 and SFTPA2 transcripts. The focus in this review is on the differential regulation of SFTPA1 and SFTPA2 with primary focus on the role of 5′ and 3′ untranslated regions (UTRs) and flanking sequences on this differential regulation as well molecules that may mediate the differential regulation.